A new ent-norabietant diterpenoid from roots of Euphorbia lathyris L. Issue 29 (18th July 2018) - Yun, Young Sook; Takeda, Yukari; Fukaya, Haruhiko; Fuchino, Hiroyuki; Kawahara, Nobuo; Takahashi, Shigeru; Takahashi, Yuji; Inoue, Hideshi
Graphical abstract: Highlights: A new ent -norabietane diterpenoid named lathyrisol A was isolated from E. lathyris. Lathyrisol A showed CHOP promoter activity in Mia Paca2 cells. Lathyrisol A is the first example of naturally occurring norabietane diterpenoid. Abstract: A new highly oxidized ent -norabietane diterpenoid named lathyrisol A (1 ) was isolated from roots of Euphorbia lathyris L. The structure and absolute configuration of 1 were elucidated on the basis of data obtained by HRESIMS, NMR, and the Cu-Kα radiation X-ray diffraction analysis. This compound is the first example of naturally occurring norabietane diterpenoid with an exocyclic olefin at the C-4 position.